Pharmacoeconomic analysis of drug supply of the military personnel with chronic bronchitis - O. V. Plieshkova; O. V. Bielozorova; M. V. Bilous; D. V. Drozdov; A. V. Nikituk (Zaporozhye State Medical University, 2021)
Despite the superiority of bronchitis in the structure of respiratory diseases in the military personnel, its course develops with certain peculiarities due to the peculiarities of military service. Consequently, the optimization of the costs of providing the military personnel with medicines is becoming more and more of medical and social importance. Reasonable selection of medicines in the treatment of chronic bronchitis is the result of the choice of effective and safe drugs, considering the cost of the components for military health care. Aim. To perform a pharmacoeconomic analysis of drug supply to the military personnel with chronic bronchitis. Materials and methods. The materials of the study were a database of drugs registered in Ukraine, presented on the official website of the State Institution "State Expert Center" of the Ministry of Health of Ukraine. The study employed "cost - effectiveness" method, which allows comparing the cost of a particular treatment method and its effectiveness. Results. The scheme of the pharmacoeconomic analysis method has been offered. According to the results of the previously formed list of drugs for the treatment of military personnel with chronic bronchitis, a further analysis of the proposed range of drugs is conducted using an expert survey. By calculating the efficacy ratio within each presented pharmacotherapeutic group, a 10-item list of the most optimal drugs for the treatment of chronic bronchitis has been compiled. Conclusions. Pharmacoeconomic analysis of medical supply to the military personnel is a constructive solution in the process of identifying manufacturers as potential suppliers of medicines to cover the needs of the medical service of the Armed Forces of Ukraine. Based on the results of the pharmacoeconomic analysis of the drug supply to military personnel with chronic bronchitis, a recommended list of drugs for their treatment has been formed. However, this list can be expanded to include drugs with the highest efficacy - according to the expert assessment. In the future it may become the basis for inclusion of drugs in the clinical protocols of medical care and could be used for the development of cost standards for the relevant nosological forms, which will improve the efficiency and quality of treatment and will provide economic benefits.